Energy partitioning in N2 microwave discharges: integrated Fokker–Planck approach to vibrational kinetics and comparison with experiments. (1st October 2022) - Altin, M; Viegas, P; Vialetto, L; van de Steeg, A W; Longo, S; van Rooij, G J; Diomede, P
Abstract: This work investigates energy transfers between electrons, vibrational and translational degrees of freedom and their effect on dissociation mechanisms in a N2 microwave plasma in the pressure range between 50 and 400 mbar. A novel self-consistent 0D plasma chemistry model describing vibrational kinetics via the vibrational energy equation and the Fokker–Planck approach is developed. It is used to simulate conditions achieved experimentally, providing good agreement with measured values of vibrational and gas temperature and electron density. Above 100 mbar, energy efficiency of dissociation increases with power density, due to the significant contribution of collisions between vibrationally excited N2 and electronically excited molecules. Energy transfer to vibrations is maximum at low power density and low pressure due to reduced gas heating.